The study of the student comfortability in Campus environment, Case study: ITSB Campus, Cikarang - Kukuh Rizki Satriaji (ARTEKS : Jurnal Teknik Arsitektur, 2017)
The old downtown area of ​​Banda Aceh holds high historical value, as evidenced by the many historic relics that still survive as a historic object in the region. The existence of these ancient artifacts can complement the historical narrative as well as the authentic proof of the identity of the city of Banda Aceh. The central area of ​​Banda Aceh requires interesting public spaces to make the existence of these historic assets more prominent as an element of the attraction of this historic area. This study aims to strengthen the identity of the downtown area of ​​Banda Aceh through an architectural design concept in a potential public corridor that has not been optimally utilized. The idea is to assemble historic spaces in this corridor to make it easier and convenient for pedestrians to access. This research is done by recording visual image of open space in public corridor area to capture visual picture and to know physical quality of public spaces in the location. Increased visual accentuation in the public corridors of the downtown area of ​​Banda Aceh can form visual sequences that provide different spatial experiences. The experience of this space arises from the historical space-themed space phases supported by the gradual display of space elements. The key to success in strengthening the identity of this corridor is the selection of the design of appropriate elements of space, in accordance with the character of space that can represent the values ​​and historical identity of the region.